Developing metacognitive teaching in Chinese language through conducting lesson study in Shanghai. Issue 1 (9th December 2020) - Shi, Lan; Cheng, Eric C.K.
Abstract : Purpose: This paper investigates the effectiveness of metacognitive teaching methods on students' reading comprehension through a lesson study case conducted in Shanghai. Design/methodology/approach: This study adopts an experimental design with control groups and experimental groups. Plan–do–check–act (PDCA) cycles of lesson study were conducted to evaluate the effectiveness of modeling, self-questioning, think aloud and KWL strategy in Chinese language lessons. Metacognitive teaching strategies were implemented at a junior high school in Shanghai. The data was collected via lesson observation, interviews and pre- and posttests. Findings: Results identified a significant difference between the incremental scores of students' reading comprehension in the experimental group and control group. The findings from the lesson observation showed that metacognitive teaching strategies in Chinese language developed students' reading comprehension. Moreover, PDCA cycles of lesson study helped the teachers improve metacognitive teaching strategies. Originality/value: Few studies have been conducted to validate metacognitive teaching through lesson study in the context of China schools, and this study contributes to a new research dimension of lesson study on developing pedagogical practices to improve student learning outcomes.